Analisis Kesulitan Belajar Siswa dalam Memahami Konsep Kimia Laju Reaksi Kelas XI IPA SMA Negeri 1 Labuapi - Salahudin, Afrianti; Savalas, Lalu Rudyat Telly; Hidayanti, Ermia (FKIP University of Mataram, 2025)
This study aims to describe the learning difficulties of students that need to be overcome in understanding the concept of reaction rate chemistry in class XI science SMA Negeri 1 Labuapi. The approach used is a qualitative descriptive approach. The subjects of this study are all students of class XI science of SMA Negeri 1 Labuapi, with samples selected using the nonprobability sampling method of saturation sampling. Data collection was carried out through a closed questionnaire on a likert scale of 5 and interviews. Data interpretation refers to five categories of learning difficulties, namely very high, high, moderately high, low, and very low, which are determined based on simple percentages and tables. The results of the data analysis showed that: 1) Students who experienced difficulties with internal factors included aspects of student ability 38.7%, student interest 37.5%, understanding of reaction rate material concepts 30%, student motivation 27.5%, included in the low category while external factors with aspects of approach/learning model 35%, teaching resources 23% were in the low category, and teachers 17%, class conditions 15% were in the very low category 2) Students' learning difficulties in understanding the concept of reaction rate chemistry that need to be considered are internal factors of student ability indicators (38.75%) and external factors in learning approaches/model indicators (35%).